Grammatical Errors in Written Reflections of English Education Master’s Program Students - Hapsari, Anita Galuh Sri; Ginting, Aprilia Arnis; Bram, Barli (citeus, 2019)
Mastering sentence structure for English Education Master’s Program (EEMP) students is obligatory considering their level of education as graduate students, who would become English teachers, lecturers, or researchers in the future. Therefore, major errors in constructing English sentences are no longer expected to happen at this level. This study investigated grammatical errors in sentences produced by EEMP students in their weekly written reflections in their Educational Psychology class. Fifty reflections of the first semester of EEMP graduate students were collected from assignments given by the lecturer of Educational Psychology class. This research employed document analysis as the method and the data analysis was conducted based on error categories. The results showed that the students made 106 morphological errors consisting of omission, addition, alternating form, archi-form, misordering, and 75 syntactical errors, including the use of the subject-verb agreement, preposition, conjunction, punctuation, and parallel structures.